Periodic solutions of differential equations with a general piecewise constant argument and applications - Kuo-Shou Chiu; Manuel Pinto (Electronic Journal of Qualitative Theory of Differential Equations, 2010)
In this paper we investigate the existence of the periodic solutions of a quasilinear differential equation with piecewise constant argument of generalized type. By using some fixed point theorems and some new analysis technique, sufficient conditions are obtained for the existence and uniqueness of periodic solutions of these systems. A new Gronwall type lemma is proved. Some examples concerning biological models as Lasota-Wazewska, Nicholson's blowflies and logistic models are treated.